2009
DOI: 10.3748/wjg.15.3153
|View full text |Cite
|
Sign up to set email alerts
|

What is the most cost-effective strategy to screen for second primary colorectal cancers in male cancer survivors in Korea?

Abstract: AIM:To identify a cost-effective strategy of second primary colorectal cancer (CRC) screening for cancer survivors in Korea using a decision-analytic model. METHODS:A Markov model estimated the clinical and economic consequences of a simulated 50-yearold male cancer survivors' cohort, and we compared the results of eight screening strategies: no screening, fecal occult blood test (FOBT) annually, FOBT every 2 years, sigmoidoscopy every 5 years, double contrast barium enema every 5 years, and colonoscopy every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, colorectal screening guidelines for the general population could underestimate the actual needs of cancer survivors. One previous study reported that for cancer survivors aged 40-years-old, colonoscopy every 5 years might be an economically feasible strategy [ 19 ]. As a baseline analysis of colorectal cancer screening, we considered all the above mentioned recommendations to be compliant with colorectal screening among lung cancer survivors ≥40 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…However, colorectal screening guidelines for the general population could underestimate the actual needs of cancer survivors. One previous study reported that for cancer survivors aged 40-years-old, colonoscopy every 5 years might be an economically feasible strategy [ 19 ]. As a baseline analysis of colorectal cancer screening, we considered all the above mentioned recommendations to be compliant with colorectal screening among lung cancer survivors ≥40 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Because to our knowledge there is no consensus regarding the optimal cancer screening strategy in Korean cancer survivors, an operational definition of appropriate screening in the current study was developed based on the National Cancer Screening Program in Korea, 28 but modified in consideration of other relevant cancer screening guidelines, [29][30][31][32] epidemiological evidence from cancer survivors 4,33 and Asians, 19,34,35 and current cancer screening practices in Korea (Table 2). 36 Recommendations for screening from physicians were also ascertained for cancer screening behaviors.…”
Section: Measures and Outcomesmentioning
confidence: 99%
“…43 Finally, we assumed that the compliance to CRC surveillance was 100% in our patient cohort, which is not an uncommon assumption in the literature. 30 To partially justify this assumption, we ensured that our cohort included only local patients who were very likely to comply with their colonoscopy surveillance schedules.…”
Section: Discussionmentioning
confidence: 99%